INNOVATIVE TECHNOLOGIES IN THE FORMATION OF MOTOR SKILLS IN BASKETBALL IN ORDER TO IMPROVE THE QUALITY OF EDUCATIONAL PROCESS - Natal’ya Borisovna Pavlyuk; Elena Vladimirovna Perevozčikova (Вестник Северо-Кавказского федерального университета)
Discusses the use of innovation oriented technologies in the classroom with the students of the Faculty of physical culture. Suggested the use of specially made glasses for different conditions of the touch control and correction movements in class basketball, enhancing the quality of the educational process.